Optimizing the Empowerment of Mediation Institutions in Banking Dispute Resolution in Indonesia - Sudiyana Sudiyana; Devi Andani (Universitas Negeri Semarang, 2024)
The development of the banking business in the digitalization era is increasingly complex, which has the potential to cause disputes with a variety of legal issues. This writing aims to examine and analyze how to empower mediation institutions in resolving business disputes in Indonesia. This writing method is included In the provisions of laws and regulations both in the Civil Code, the Law on Banking, Law Number 30 of 1999 concerning Alternative Dispute Resolution and Arbitration, including technical regulations at the Judicial level such as Supreme Court Regulation Number 1 of 2016 regarding Mediation, it has been regulated regarding the Mediation settlement mechanism. There are various factors that affect mediation institutions that cannot be carried out optimally, namely, banking mediation regulations are inadequate, lack of public understanding (customers), weak banking mediation institutions, weak implementation of mediation. It is necessary to make a social-comprehensive legal breakthrough so that mediation institutions can be empowered more optimally in resolving banking disputes.